Hypopigmentation: a common feature of Prader-Labhart-Willi syndrome. - Butler, M G (1989)
In order to determine the frequency and characterization of hypopigmentation in Prader-Labhart-Willi syndrome (PLWS), clinical, cytogenetic and biochemical findings are reported in 56 PLWS individuals. Forty-eight percent of the individuals with PLWS met the criteria for hypopigmentation. Hypopigmentation in PLWS individuals appears to be as common as previously recognized features such as behavioral problems and dental abnormalities. Significant differences in hair color, sun sensitivity, and complexion were found between those PLWS patients with the chromosome 15 deletion and those with normal chromosomes. Individuals with the deletion frequently had lighter hair color, more sun sensitivity, and fairer complexion than did either other family members or nondeletion PLWS patients. No significant differences in biochemical findings (phenylalanine, tyrosine, catecholamines, or beta-melanocyte-stimulating hormone) were found between deletion and nondeletion PLWS patients or between hypopigmented and normally pigmented patients. The data suggest that a gene(s) controlling the activity of tyrosinase or other enzymes required for melanin production is located on proximal 15q.